Privateers of the Americas : Spanish American Privateering from the United States in the Early Republic - Head, David (Historian) (Book collections on Project MUSE., 2015)
"Privateers of the Americas examines raids on Spanish shipping conducted from the United States during the early 1800s. These activities were sanctioned by, and conducted on behalf of, republics in Spanish America aspiring to independence from Spain. Among the available histories of privateering, there is no comparable work. Because privateering further complicated international dealings during the already tumultuous Age of Revolution, the book also offers a new perspective on the diplomatic and Atlantic history of the early American republic."--Cover